First report on the leafminer fly Lyriomiza trifolii (Diptera: Agromizydae) attacking coffee plantations - Silva, Ítalo; Ribeiro, Luan; Gorri, Jéssica; Alves, Flávia; Fernandes, Flávio (Coffee Science - ISSN 1984-3909, 2015)
Liriomyza trifolii has become a serious pest for numerous crops. This is the first report of L. trifolii attacking coffee plants. Thus, the objective of this study is to record the occurence of this insect in Municipality of Alto Paranaíba, State of Minas Gerais, Brazil. Coffee leaves with mines of L. trifolii were reported in five states (MG, SP, ES, BA and PE). The population peaks occur after a period of low rainfall 11.5 mm/month and 7.11 mm/month. This pest has not been reported.